Lithofacies Types, Assemblage Characteristics, and Sedimentary Evolution Model of Lacustrine Shale in Dongyuemiao Formation of Fuxing Area - Shu, Yi; Bao, Hanyong; Zheng, Youheng; Chen, Miankun; Lu, Yongchao; Liu, Haotian; Peng, Wei; Zhou, Lin; Ma, Yiquan; Wen, Yaru; Wang, Qiming; Zhang, Zhiyao (Frontiers in Earth Science, 2021)
The identification and classification of lithofacies’ types are very important activities in shale oil and gas exploration and development evaluation. There have been many studies on the classification of marine shale lithofacies, but research on lacustrine shale lithofacies is still in its infancy. Therefore, in this study, a high-resolution sequence stratigraphic framework is established for the lacustrine shale of the Jurassic Dongyuemiao Formation in the Fuxing area using detailed core observations, thin section identification, XRD analysis, major and trace element analysis, wavelet transform analysis, and detailed identification and characterization of the fossil shell layers in the formation. In addition, the lithofacies’ types and assemblages are identified and characterized, and the lithofacies’ characteristics and sedimentary evolution models in different sequence units are analyzed. The significance of the lithofacies assemblages for shale oil and gas exploration is also discussed. The results show that the shale of the target interval can be divided into 8 parasequence sets; further, 9 types of lithofacies and 6 types of lithofacies assemblages are identified. The 9 lithofacies are massive bioclast-containing limestone shoal facies (LF1), thick-layered fossil shell–containing limestone facies (LF2), layered mud-bearing fossil shell–containing limestone facies (LF3), laminated fossil shell–containing argillaceous shale facies (LF4), laminated fossil shell–bearing argillaceous shale facies (LF5), argillaceous shale facies (LF6), massive storm event–related bioclast-containing facies (LF7), massive argillaceous limestone facies (LF8), and massive mudstone facies (LF9). The sedimentary evolution models of different lithofacies are established as follows: Unit 1 (LF1-LF6) of the Dong-1 Member corresponds to the early stage of a lake transgressive system tract, and Units 2–4 (LF4-LF7) correspond to the middle to late stage of the lake transgressive system tract, which was an anoxic sedimentary environment. The Dong-2 Member (LF7-LF8) and the Dong-3 Member (LF5+LF9) correspond to a lake regressive system tract, which was an oxygen-rich sedimentary environment. Based on the characteristics of the shale lithofacies, sedimentary environment, and the quality of the reservoir, the lithofacies assemblage of LF4–LF7 in Unit 4 is the most favorable type for oil and gas exploration, followed by the lithofacies assemblage in Unit 2; the lithofacies assemblage in the Dong-2 and Dong-3 Members are the worst.